When girls do masculinity like boys do : establishing gender heteroglossia in school mathematics participation - Jaremus, Felicia (Mathematics education research journal, 2021)
While mathematics education research has become increasingly concerned with issues of equity, including girls' participation in the subject, the field remains troubled with conceptualising and operationalising gender. To date, few studies of gender and school mathematics participation have moved beyond conflating gender with sex or categorising masculinities and femininities through the body. This failure to engage with gender conceptualisation has persisted despite the apparent intractability of girls' underrepresentation in senior secondary mathematics in many contexts, including Australia. In this article, I provide fresh insights into girls' mathematics participation by employing a conceptualisation of gender as heteroglossic to explore the post-compulsory mathematics participation choices of two school students, one girl and one boy. Using these theoretical tools to decentre the students' bodies, I demonstrate that the reasons why these students chose to participate in Mathematics Advanced do not distinguish them by their sex/gender, as would be expected in the monoglossic gender system. While femininity was performed, both students' subject choices were primarily characterised as masculine performances, including establishing themselves as having mathematics brains and seeking to use their mathematics participation to attain prestige. I argue that recognising and normalising girls' masculinity and boys' femininity, rather than simply categorising gender differences, will be essential to increasing girls' belonging and participation in mathematics. This will require greater attention to the differences within, and similarities between, the categories of boy and girl. [Author abstract]